An investigation of the knowledge of HIV/AIDS education amongst the 15 year old girls at Kiriyatswane secondary school - Mashabela, Marei Cyprian (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2006.